Seasonal variation of intestinal Tapeworms in Gallus gallus domesticus at Ahmednagar region - Shukla, S J; Borde, S N; Humbe, Atul; Bhavare, V V (International Multidisciplinary Research Journal, 2012)
The present paper deals with the seasonal variation of tapeworms in Gallus gallus domesticus at Ahmednagar region, high prevalence of Raillietina parasite are occurred in winter season followed by summer season and low in rainy season. This type of results indicates that environment factors and feeding habitats are influencing that seasonality of parasitic infection either directly or indirectly.